EARLY OUTCOMES OF LAPAROSCOPIC SURGERY FORCOMMON BILE DUCT STONES IN THE ELDERLY - Nghị, Nguyễn Hữu; Khanh, Phạm Công; Nghị, Lê Thanh (Journal of Health and Aging, 2025)
This study was conducted to describe the clinical and paraclinical characteristics and evaluate early outcomes of laparoscopic surgery for common bile duct (CBD) stones in elderly patients. We performed a retrospective study of 95 patients over 60 years of age diagnosed with CBD stones who underwent laparoscopic surgery at the Hepatobiliary Surgery Department, Thong Nhat Hospital from January 2016 to December 2022. Among the 95 surgical cases, there were 49 male patients (51.58%) and 46 female patients (48.42%), with a mean age of 74.67 years (ranging from 60 to 95 years). Regarding clinical manifestations, abdominal pain was the most common symptom, present in 91.58% of patients, followed by cholangitis in 41.05% (39 cases). Post-surgery, the stone clearance rate reached 94.7%, demonstrating the high effectiveness of the laparoscopic approach. The mean operative time was 136.36 ± 23.26 minutes, and the average hospital stay was 13.4 ± 3.8 days. Postoperative complications were documented, including bile leakage (3.16%), bleeding (1.05%), and infection (2.11%). Notably, no mortality was recorded in this study. The findings indicate that laparoscopic surgery for CBD stones in elderly patients at Thong Nhat Hospital is a safe and feasible procedure, provided that patients are carefully selected preoperatively. This study contributes additional evidence supporting the efficacy and safety of laparoscopic surgery in treating CBD stones in elderly patients, who typically present with more comorbidities and higher risk of complications compared to younger patient groups. The low complication rates and absence of mortality in our series suggest that, with proper patient selection and surgical expertise, advanced age should not be considered a contraindication to laparoscopic CBD stone management.
Keywords: Common bile duct(CBD); elderly; laparoscopic